Remarriage among older immigrants and their host country peers – a countrywide study - Liversage, Anika (Migration Letters, 2021)
With immigrants across Europe ageing in increasing numbers, this article uses Danish administrative data to map the unexplored remarriage patterns among three groups of older immigrants and compare them to their Danish host country peers. Results show that remarriage late in life is uncommon. When it occurs, men remarry more often than women, with the gender difference many times larger among immigrants. For choice of spouse, most marriages are endogamous, with immigrants predominantly finding spouses transnationally. The data also reveal a distinct age pattern in all groups, with wives substantially younger when marriages are transnational, i.e. when wives arrive as marriage migrants. In addition to extending the literature on remarriage in old age to include immigrant groups, this study also documents both the centrality of older immigrants finding spouses transnationally and the existence of substantial age differences in transnational remarriages, regardless of whether husbands are immigrants or not.